Model characteristics of special physical preparedness of Juvenile category athletes in acrobatic rock'n'roll - Humeniuk, S. (Slobozhanskyi herald of science and sport, 2018)
Purpose: develop model characteristics of special physical readiness of Juvenile category athletes in acrobatic rock'n'roll.